Optical coherence elastography detects increased corneal stiffness in nonhuman primates with experimental glaucoma - Singh, Amandeep; Nair, Achuth; She, Zhihui; Dehshiri, Mohammed; Singh, Manmohan; Aglyamov, Salavat; Patel, Nimesh; Larin, Kirill (Journal of biomedical optics, 2025)
Glaucoma is a leading cause of irreversible blindness, characterized by progressive optic nerve damage. Early detection of glaucoma is key to effective intervention, but an incomplete clinical understanding of the development of glaucoma complicates the selection of diagnostic criteria. Prolonged ocular hypertension due to glaucoma can impact the biomechanical properties of ocular tissues, including the cornea. We examine whether experimental glaucoma causes changes in the biomechanical properties of the cornea. We determined the biomechanical properties of the cornea in a nonhuman primate model of unilateral experimental glaucoma and compared them with the fellow, untreated control eyes using optical coherence elastography (OCE) to determine if prolonged intraocular pressure (IOP) elevation causes changes in corneal stiffness. Experimental glaucoma was induced in one eye ( , ) by lasering the trabecular meshwork, whereas the fellow eye was used as a control. Both eyes were imaged with wave-based OCE to investigate the inter-ocular difference in stiffness. Measurements were taken at three different frequencies with quasi-harmonic excitation, and central corneal thickness was measured along with IOP in each eye. Our results show a significant ( ) increase in wave speed in the experimental glaucoma eye compared with the control eye for both subjects. These results show the potential of wave-based OCE methods for assessing stiffness changes in the cornea caused by remodeling due to chronic pressure elevation.